ALK-positive histiocytosis of the umbilicus with KIF5B-ALK fusion: A case report and review of the literature - Yili Zhu; Jun Fan; Huaxiong Pan; Bo Huang; Ying Wu; Heshui Shi; Xiu Nie (Elsevier, 2021)
Background: Since the first report in 2008 of cases of anaplastic lymphoma kinase (ALK)-positive histiocytosis, originally described as a systemic, self-limiting disease in infants, the range of ALK-positive histiocytosis has been expanded to include localized diseases in older children and adults. Case presentation: We present the case of an 18-year-old woman with a periumbilical painless mass for 5 months who underwent resection of the mass. Pathological examination showed that the tumour consisted predominantly of fascicular to storiform growth of nonatypical spindle cells admixed with lymphocytic infiltrates. The tumour spindle cells were diffusely positive for CD68, CD163 and ALK. Further molecular tests revealed an ALK gene fusion with Kinesin Family Member 5B (KIF5B) (E24)-ALK (E20), confirming ALK-positive histiocytosis. Follow-up at one and a half years after resection showed no tumour recurrence. Conclusion: Remission of ALK-positive histiocytosis in local lesions can be achieved by complete resection, and clinical follow-up shows a favourable prognosis.